Awareness of cervical cancer and its risk factors among female students of a pre university college in Bangalore, Karnataka, India - T. S., Monisha; A., Santosh (International Journal Of Community Medicine And Public Health, 2016)
Background: Cervical cancer is a serious public health problem. It is the commonest cancer among women in rural India, and India has the largest burden of cervical cancer patients in the world. Primary intervention focusing on creating awareness in the community will make a difference in present situation of cervical cancer in the country. Objective of the study was to assess the awareness of cervical cancer and its risk factors, Pap smear testing and HPV vaccine among female students of a pre university College. Methods: A cross sectional study was conducted among female students of a pre University College, near to Raja Rajeshwari Medical College and Hospital. The study was carried out for duration of two months, May and June 2016. A pre tested, semi-structured questionnaire was designed to evaluate their basic awareness on cervical cancer. After the data collection Health education on cervical cancer was given to the students. Results: Out of 98 students who participated in this study 53 (54%) students were 1st year and 45 (46%) were 2nd year students. Awareness about role of hereditary factor as a risk of cervical cancer was present in 19% of the students and 36% of the students reported that having multiple sexual partners is a risk factor for cervix cancer.45% were not aware of the fact that poor personal hygiene could also be a risk factor. 66% were not aware about HPV vaccine. There was no statistically significant association between place of residence and awareness level and there was a statistically significant difference in the awareness level and the year of study (p<0.003). Conclusions: There was statistically significant difference in the awareness level between 2nd year and 1 year student. Almost all students haven't heard about Pap smear test. Majority of the students weren’t aware about HPV Vaccine.